Relationship between supply, demand and opportunity of interior designers graduates in Malaysia construction industry - Rostam, Rostam Yaman; Adnan, Hamimah; Ahmad, Noraini; Ismail, Farrah Zuhaira; Rosman, Muhammad Redza (MAGNT Research Report, 2015)
The aim for the paper is to identify the Interior Designer (ID) graduate create by various public universities, demand of their professional services and knowledge and also opportunity in the Malaysia construction industry. The understanding towards the topic is enhanced by questionnaire response method where the related respondents are required to answer a number of questions. The chosen samples for this research are graduates who are currently practice in various ID Consulting Offices and similar. Outcome from the research shown that respondents agreed and there is still a need for improvement. Based on Malaysia cases, it is imperative that the continuance of these ‘SDO’s as the required needs of ID graduates is still below demands.